Data, phenomena and theories - Guerrero Pino, Germán (Estudios de Filosofía, 2012)
This paper presents the model of three levels of scientific knowledge (data, phenomena and theories) bearing on the recent results of the actual Philosophy of Science obtained through two particular philosophical perspectives: The New Experimentalism and the Semantic Approach of Theories. In order to do so, it contrasts of the main approaches of these two perspectives with the model of two levels of scientific knowledge (observation and theory) which belong to Logical Positivism, and that dominated the outlook of the Philosophy of Science during the first six decades of the 20th Century.